2013
DOI: 10.1007/s10008-013-2016-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant on the morphology and capacitive performance of porous NiCo2O4

Abstract: A promising nickel cobaltite oxide (NiCo 2 O 4 ) composite electrode material was successfully synthesized by a sol-gel method and followed by a simple sintering process. The microstructure and surface morphology of NiCo 2 O 4 modified by hexadecyltrimethylammonium bromide (CTAB) and polyvinyl alcohol were physically characterized by powder X-ray diffraction and scanning electron microscopy. Meanwhile, electrochemical performance was widely investigated in 2 M KOH aqueous electrolyte using cyclic voltammetry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Since this pioneering work, several researchers have been devoted on this sol-gel approach. [61][62][63][64][65] The typical preparation process is illustrated in Fig. 5a and the mechanism of gelation can be explained by the following reaction sequence in which M represents nickel or cobalt ions, and A À represents Cl À or NO 3 À ions.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this pioneering work, several researchers have been devoted on this sol-gel approach. [61][62][63][64][65] The typical preparation process is illustrated in Fig. 5a and the mechanism of gelation can be explained by the following reaction sequence in which M represents nickel or cobalt ions, and A À represents Cl À or NO 3 À ions.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…By using citric acid as the chelating ligand and H 2 O-DMF as solvent via a facile sol-gel process, the submicron-sized NiCo 2 O 4 particles exhibited a specic capacitance of 217 F g À1 with a high mass loading of 5.6 mg cm À2 . While Kong et al 61 developed a sol-gel process by adding different surfactants, such as hexadecyltrimethylammonium bromide (CTAB) and polyvinyl alcohol (PVA), to control the microstructure and surface morphology of the NiCo 2 O 4 nanoparticles. The product modied by CTAB shows the highest specic capacitance of 1440 F g À1 at a current density of 5 mA cm À2 .…”
Section: Sol-gel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all, H2 possess a higher value of specic capacitance value. Recently, Kong et al 52 reported on the effect of surfactants (CTAB and PVA) and their concentration on the morphology and capacitive performance of porous NiCo 2 O 4 . The specic capacitance was enhanced from 1063 F g À1 to 1440 F g À1 and 1263 F g À1 for 0.025 g CTAB and 0.075 g PVA.…”
Section: Xps Analysismentioning
confidence: 99%
“…Thus the morphology and microstructure of NiCo 2 O 4 controlled by CTAB possess higher specific capacitance with capacity retention of about 94.1 % over 1000 cycles. [33] Meanwhile, Ye Qin Wu and his coworkers stated that apart from processing parameters, the initial molar concentration, reaction time, and solvent too plays a critical role in preparing targeted products. Using citric acid as a chelating agent and H 2 O-DMF as a solvent, they created NiCo 2 O 4 coral-like porous crystals, sub-micron sized NiCo 2 O 4 particles, and NiCo 2 O 4 nanoparticles through Sol-gel.…”
Section: Sol-gel Processmentioning
confidence: 99%